The Efficiency of Islamic General Insurance Using Data Envelopment Analysis (DEA): Evidence From Indonesia - Novi Puspitasari; Laili Fauziyah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – The purpose of this study is to analyze the efficiency level of sharia general insurance in Indonesia. Methodology/approach – This study uses the Data Envelopment Analysis (DEA) method with output orientation. The objects in this study were 8 general insurance companies in Indonesia during the 2015-2020 period. The variables used consist of input variables (total assets, capital/equity, operating expenses, claim payments) and output variables (investment income, tabarru' funds, profit). Findings – There are three Sharia General Insurance Companies in efficient condition during the study period, namely Allianz Utama Indonesia Insurance, Sinar Mas Insurance, and Bumiputeramuda General Insurance. In addition, there were five companies in an inefficient condition during the study period, namely PT Asuransi Bringin Sejahtera Artamakmur, PT Asuransi Ramayana, PT Asuransi Staco Mandiri, PT Asuransi Umum Mega, and PT Asuransi Wahana Tata. Novelty/value – The contribution of this research is to provide an efficiency analysis of Sharia General Insurance companies in Indonesia using several inputs and outputs. Keywords Efficiency, Islamic Insurance, Data Envelopment Analysis (DEA).